Diagnóstico de la producción y comercialización del cultivo de mora (Rubus glaucus) de castilla en el cantón Pangua provincia de Cotopaxi año 2014 - Basantes Morales, Alexandra Pilar (2015)
In this research, it was found as the main problem the marketing and production of the blackberry (Rubus glaucus), for which the general objective was: To diagnose the production and marketing of the crop of blackberry (Rubus glaucus), for that reason were considered the following specific objectives, to identify the main production problems of the blackberry crops, to identify ways of marketing that producers have access, to know production costs of the blackberry, as methodology the survey was used which consisted of eighteen questions to producers and five questions to the merchants in the area of which was sampled to 244 farmers and 7 merchants….